Mimetic isomorphism as competitive strategy in the dimension stone sector - Guidi, Antonio Carlos; Pizzinatto, Nadia Kassouf; Pizzinatto, Andrea Kassouf; Monteiro, Thel Augusto; Montebello, Maria Imaculada de Lima (Revista de Negócios, 2024)
This article investigates the existence of mimetic isomorphism (MI) in companies in the dimension stone sector (DSS). The southeast of the country was taken as a base since it currently contains the highest level of technological organizational development in the sector. Thus, the overall objective of this study is to analyze which factors in the southeast region favor the practice of MI in the DSS. The study uses distinct models of statistical analysis, such as exploratory factor analysis, and Confirmatory Analysis, thus seeking to legitimize the results of organizational research. The mechanisms underlying the presence of isomorphism served as a starting point to analyze organizational behavior in this period of increasing technological advancement in the sector. It was so, detected as a guiding factor to obtain industrial investment. The research implications are restricted to the regionalization of information sources, a fact which, may be relevant for other regions of the country, since the southeast region accommodates the largest processing center for this field of economic activity. Future research should concentrate on other regions, for a comparative analysis of the results obtained, since this will enable us to outline an isomorphic behavior profile in socio-economic terms and on a national level.